2012
DOI: 10.1007/978-3-642-28714-5_4
|View full text |Cite
|
Sign up to set email alerts
|

How Architects See Non-Functional Requirements: Beware of Modifiability

Abstract: Abstract. This paper presents the analysis and key findings of a survey about dealing with non-functional requirements (NFRs) among architects. We find that, as long as the architect is aware of the importance of NFRs, they do not adversely affect project success, with one exception: highly business critical modifiability tends to be detrimental to project success, even when the architect is aware of it. IT projects where modifiability is perceived to have low business criticality lead to consistently high cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Poort et al [18] found a statistical correlation between the verification of NFRs and project success. According to their results, the benefits of verification are also more significant if NFRs are verified in early stages of a project.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Poort et al [18] found a statistical correlation between the verification of NFRs and project success. According to their results, the benefits of verification are also more significant if NFRs are verified in early stages of a project.…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies [7,8,13] propose solutions for specifying architectural invariants. Other studies [1,18,19,10] rank non-functional qualities (e.g., performance, usability, availability, etc.) by carrying out surveys.…”
Section: Introductionmentioning
confidence: 99%
“…[13] [29,30] Elicitation E1 In requirements elicitation, the focus is on FRs, not on QRs. [5,4,31,24,32,27] E2 Many QRs remain undiscovered.…”
Section: Id Research Statement Pro Conmentioning
confidence: 99%
“…The research proposed by Vara et aI., [14] aims to gain new insights into the importance of NFR in industry, the results of the study provide novel empirical evidence about the perceived importance of NFR types in industry and how it may vary. Also, we can find a detailed study on NFR impact on project success or failure in [15] [16].…”
Section: B On Non-functional Requirementsmentioning
confidence: 99%